Tinjauan Hukum Islam Tentang Sistem Sewa Tanah Dalam Kegiatan Pertanian - Deka Meuthia Novari; Iqbal Ardiansyah (STAI Al-Ma'arif Way Kanan, 2021)
Leasing can be interpreted as a contract that sells and trades between the benefits of goods and a number of rental fees. In practice, the cultivator of the land is from the tenant of the land until a certain time limit according to the expiration of the lease agreement so that the land tenant must pay the rental fee for the land he agreed to to the land owner. residents of the Pakuon Building Village. Qualitative research methods are research methods based on the philosophy of postpositivism, used to examine the condition of natural objects, this type of research is field research with qualitative descriptive research properties. Researchers used several methods, namely interviews and documentation. Interviews were conducted on 4 people with land owners and 4 people on leasing. Based on the results of the research that has been carried out, the implementation of the land lease agreement for agricultural activities in Kampung Gedung Pakuon is in accordance with the pillars and terms of the lease in the review of Islamic law and does not conflict with the texts of the Qur'an and Sunnah. Agriculture is an activity in the processing, utilization of a land by planting a plant in farming activities. As for the practice of leasing, the land tenant works on or cultivates the land of the land owner so that the vacant land can be used for agricultural activities within the period agreed upon in the collective agreement. So of course both parties, both the land owner and the land tenant, do not feel disadvantaged